Produksi Bioetanol Dari Pati Sorgum Dengan Penambahan Tween 80 Dan Ekstrak Cordyceps Sinesis Myecelium : Variasi Konsentrasi Inokulum - Bonita Esther FS; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Energy demands are still dependent on fossil fuels such as oil, coal and gas lead to the depletion of fossil resources (oil, natural gas, and coal). To overcome the dependence onfossil fuels, sorghum starch conversion into bioethanol as a renewable energy. In this research, sorghum starch saccharification process using enzymes α-amylase andglucoamylase and fermented by Saccharomyces cerevisiae using the method of simultaneous saccharification and fermentation (SSF) with addition of tween 80 and Cordyceps sinensis mycelium extract as supplement. The purpose of this study was to determine the effect of inoculum concentration and time of the acquisition bioethanol fermentation, fermentation was conducted in a 2L fermentor with variations of fermentation time: 24, 48, 72, and 96 hours and concentrations inoculum 2% (w/v), and 2.5% (w/v) with the addition of tween 80 0,2% (v/v) and Cordyceps sinensis mycelium extract as much as 0.5 gr/l. The higherconcentration of inoculum, the more the number of cells and the higher the bioethanol yield while the residual sugar content produced less and less at the end of fermentation. Sorghumstarch fermentation process produces the best conditions on the inoculum concentration of 2.5% (w/v) and fermentation time 72 hours with bioethanol about 1,320 (%v/v).Key words: α-amylase, bioethanol, cordyceps sinensis mycelium, glucoamylase, saccharomyces cerevisiae, simultaneous saccharification and fermentation, tween 80